Physiological and psychological recovery in two pure forests: interaction between perception methods and perception durations - Sun, Xiaogang; Li, Qinglan; Zhang, Xin; Sun, Miao; Yin, Jiahui; He, Jingyi; Zhong, Yige; Ning, Wei (Frontiers in Public Health, 2024)
The forest experience is good for people's physical and mental health. However, there are few studies on the effects of pure forest based on the duration and way of experience on people's physical and mental recovery. In this study, we took 180 first-year college students as research objects and conducted experiments in Pinus sylvestris var. mongolica and Betula platyphylla and the control group of Grass plot.The changes of physiological and psychological indexes of the subjects were compared by two perception methods (onsite perception, video perception) and three perception duration (10 minutes, 20 minutes, 30 minutes). The results showed that :(1) the difference between the two pure forests was mainly reflected in the short-term recovery of diastolic blood pressure (DBP) and the long-term recovery of total mood disorder (TMD). ( 2) Video perception is more conducive to short-term recovery of systolic blood pressure (SBP) and diastolic blood pressure (DBP). (3) Viewing the Pinus sylvestris var. mongolica for 20 minutes in different ways is the best way to relieve stress. It is suggested that in the future forest landscape construction, Pinus sylvestris var. mongolica can be used as the rehabilitation perception material, and reasonable path length or perception time can be selected for design. These results can provide scientific basis for future landscape design based on forest health and environmental perception.